Consumer Self-Identity, Emotions, Ethical Beliefs, and Authenticity about Ethical Purchasing of Consumer Goods for a Circular Economy Model - Vasiliki LEMONIDOU; George SPAIS (Journal of Emerging Trends in Marketing and Management)
We examine how consumers' feelings of guilt and their ethical beliefs—precisely idealism and relativism—impact their purchasing decisions related to Greece's Circular Economy Model (CEM). By focusing on customer satisfaction and engagement, we aim to understand better how consumers interact with sustainable products within the circular economy, building upon Burke and Reitzes' (1981) Self-Identity Theory (SIT). Additionally, we explore how consumer authenticity influences the relationships between moral beliefs, guilt, and ethical purchasing behavior. A structured online questionnaire was distributed via Google Forms to address three research objectives. It included nine demographic and six structured questions. A convenience sample of 371 respondents from Athens, Thessaloniki, Patras, and Heraklion, consisting of Hellenic Open University students and coworkers buying eco-friendly products, participated. Statistical analysis tested seventeen research hypotheses, supporting eleven, rejecting five, and yielding inconclusive evidence for one. The study reveals a nonlinear positive association between ethical beliefs and three key factors: ethical purchasing behavior, purchase intention, and adopting sustainable consumer practices. Additionally, a linear positive relationship exists among adopting sustainable consumer behaviors, ethical purchasing behavior, and ethical purchase intention. The connections between ethical beliefs and the adoption of sustainable consumer practices, as well as those between ethical beliefs and ethical purchase intention, are influenced by consumer authenticity. The findings of this study have critical theoretical, research, managerial, and practical implications for academics and marketing managers, supporting the initial assumptions.